SIMULATION OF CAPACITY AND REQUIREMENTS OF DROP STRUCTURE ONMULTIBENCH OVERBURDEN DUMP - Faridh, Adam
Mining activity is the process of extracting mineral resources from the earth. One of the outcomes of this mining activity is overburden rocks that will be stacked in an open area. The consequence of placing overburden rocks in an open area is their direct interaction with rainwater. The rainwater that falls and flows on the ground surface is referred to as surface runoff. Management of surface runoff is necessary to prevent erosion of the overburden rocks and disruption of mining operations. Rainfall runoff is analyzed based on the Synthetic Unit Hydrograph (SCS) method with daily rainfall data for return periods ranging from 2 to 25 years. The rainfall catchment area is determined based on the designated catchment area size, as per the applicable regulations. Rainfall runoff is analyzed under two scenarios. Scenario 1 involves the placement of drop structures that cut straight across the multibench, while scenario 2 involves the placement of drop structures parallel to the multibench, dividing the rainfall catchment area into two at the second bench. Capacity to convey discharge is determined by comparing the Synthetic Unit Hydrograph (SCS) for each scenario. Meanwhile, the need for drop structures is determined by comparing the discharge generated by each scenario with the available drainage facilities. The research results, which simulate two scenarios, indicate that the XYZ study area has a rainfall intensity of 40,92 m3/hour with a 10-year return period. The simulation results for using drop structures on the multibench overburden rocks with a slope of 26° show a reduction in the initial Froude number from 6.34 to 0.40 with a drop height of 1 m and a total of 10 drops. In this simulation, the drop structure capacity for scenario 1 has peak discharge rates of 0.24 m3/s at outlet 1, 0.48 m3/s at outlet 2, and 0.72 m3/s at outlet 3. As for scenario 2, peak discharge rates are 0.24 m3/s for outlet 1, 0.22 m3/s for outlets 2a and 2b, and 0.65 m3/s for outlet 3. The peak times for each outlet in Scenario 1 are 1.15 hours for outlet 1, 1.21 hours for outlet 2, and 1.28 hours for outlet 3, while for scenario 2, peak times are 1.15 hours for outlet 1, 1.31 hours for outlets 2a and 2b, and 1.38 hours for outlet 3. the required drop structure with a discharge of 0.79 m3/s is the scenario 2 with a peak discharge of 0.65 m3/s.